Perspectives on validation of clinical predictive algorithms - de Hond, Anne A. H.; Shah, Vaibhavi B.; Kant, Ilse M. J.; Van Calster, Ben; Steyerberg, Ewout W.; Hernandez-Boussard, Tina (NPJ digital medicine, 2023)
The generalizability of predictive algorithms is of key relevance to application in clinical practice. We provide an overview of three types of generalizability, based on existing literature: temporal, geographical, and domain generalizability. These generalizability types are linked to their associated goals, methodology, and stakeholders.